2012
DOI: 10.1590/s0103-50532012000600013
|View full text |Cite
|
Sign up to set email alerts
|

ESI-MS study of speciation in hydrolyzed aluminum chloride solutions

Abstract: Soluções de AlCl 3 foram analisadas em concentrações de 0,03 a 5,0 mmol dm-3 e pH de 3,5 a 6,0 por espectrometria de massas com ionização por electrospray e analizador quadrupolar (ESI-Q-MS). Esses dados espectrais foram comparados com os obtidos por ressonância magnética nuclear (NMR) de 27 Al e potenciometria. Espécies resultantes da hidrólise do cátion alumínio em solução apresentaram-se principalmente como complexos carregados positivamente (+1) com moléculas de água coordenadas (n = 1-3) ao metal. As anál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…It is evident that [Al(OH) 2 (H 2 O) 2 ] 1+ species is the most stable among the five [Al(OH) 2 (H 2 O) n ] 1+ ( n = 0–4) species. This result is in perfect agreement with the recent ESI-Q-MS data, , in which the [Al(OH) 2 (H 2 O) 2 ] 1+ species was strikingly observed ( m / z = 97) in AlCl 3 solution over a pH range of 3.06 to 4.20. , For [Al(OH) 3 (H 2 O) n ] 0 ( m = 3) species, two distinct regions are obviously visible. When n varies from 0 to 1, the Δ G visibly decreases, whereas the Δ G evidently increases with increasing n at high n (≥1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It is evident that [Al(OH) 2 (H 2 O) 2 ] 1+ species is the most stable among the five [Al(OH) 2 (H 2 O) n ] 1+ ( n = 0–4) species. This result is in perfect agreement with the recent ESI-Q-MS data, , in which the [Al(OH) 2 (H 2 O) 2 ] 1+ species was strikingly observed ( m / z = 97) in AlCl 3 solution over a pH range of 3.06 to 4.20. , For [Al(OH) 3 (H 2 O) n ] 0 ( m = 3) species, two distinct regions are obviously visible. When n varies from 0 to 1, the Δ G visibly decreases, whereas the Δ G evidently increases with increasing n at high n (≥1).…”
Section: Resultssupporting
confidence: 92%
“…17 On the other hand, Tanaka's group reported that the aluminum species existed mainly as [Al(OH) 2 (H 2 O) 2 ] + , [Al(OH) 2 Cl 2 ] − , [Al(OH)Cl 3 ] − , and [AlCl 4 ] − in AlCl 3 solution with a pH of 3.7, using an electrospray ionization quadrupole mass spectrometer (ESI-Q-MS). 18 Đurđevic's group suggested that the hydrolytic aluminum species were present mainly as [Al(OH) 2 (H 2 O)] + and [Al(OH) 2 (H 2 O) 2 ] + in AlCl 3 solution with a pH of 4.20, using ESI-Q-MS. 19 It is obvious that both single-hydroxyl [Al(OH)(H 2 O) 4 ] 2+ and double-hydroxyl [Al(OH) 2 (H 2 O)] + and [Al(OH) 2 (H 2 O) 2 ] + complexes are the crucial aqueous Al III complexes at a pH of around 4.0. Experimental and theoretical studies indicate that the hydrolysis of trivalent aluminum ions is strongly dependent also on possible coordination species in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Cvijović and Djurdjevic in some papers (Cvijović et al, 2012(Cvijović et al, , pp.1087(Cvijović et al, -1097, (Cvijovic et al, 2012, pp.313-322), (Djurdjevic et al, 2005(Djurdjevic et al, , pp.1615(Djurdjevic et al, -1629 presented the results of studing monomeric species, polymeric species that form during complexation and hydrolysis of Al 3+ ions and amino acids and antibiotics. By varying a degree of neutralization, metal-organic ligand ratio, temperature, pH, the aging time of the Al-solution, mixing speed, different equilibrium species of aluminum and organic molecules are formed and with different yields.…”
Section: +mentioning
confidence: 99%
“…In aqueous solutions, aluminium ions easily undergo hydrolysis owing to their high affinity to negatively charged hydroxyl groups. Hydrolysis products of aluminium chloride solutions have been extensively studied . Other than hydroxyl and chloride complexes of aluminium, various aluminium fluoride complexes [Al–F complexes] form spontaneously in aqueous solutions at extremely low concentrations of Al and F with high stability constants and are highly toxic .…”
Section: Introductionmentioning
confidence: 99%
“…Electrospray ionization quadrupole mass spectrometry (ESI‐Q‐MS) has been used for the identification of Al species present at low concentrations in natural water . This technique ensures that the metal ions will be maintained in their “original dissolved form” .…”
Section: Introductionmentioning
confidence: 99%